Complete mitochondrial genome of the endangered freshwater fish Microphysogobio rapidus (Cypriniformes, Cyprinidae) from Korea. Issue 1 (2nd January 2020) - Kim, Kang-Rae; Bang, In-Chul
Abstract: Microphysogobio rapidus is an endangered freshwater fish from Korea with a limited distribution in the Nakdong River. Here, we determined the mitochondrial genome of M. rapidus, which consisted of 16, 603 bp with 13 protein-coding genes, 2 ribosomal RNAs, 22 transfer RNA genes, and a control region (D-loop). The overall base composition of the complete genome was 29.96% A, 26.06% T, 17.24% G, and 26.74% C, with high A + T content of 56.02%.